Cold Treatment Breaks Dormancy but Jeopardizes Flower Quality in Camellia japonica L. - Berruti, Andrea; Christiaens, Annelies; Keyser, Ellen De; Labeke, Marie-Christine Van; Scariot, Valentina (Frontiers in Plant Science, 2015)
Camellia japonica L. is an evergreen shrub whose cultivars are of great ornamental value. In autumn, after flower bud differentiation, dormancy is initiated. As in many other spring flowering woody ornamentals, winter low temperatures promote dormancy release of both flower and vegetative buds. However, warm spells during late autumn and winter can lead to unfulfilled chilling requirements leading to erratic and delayed flowering. We hypothesized that storing plants at no light and low temperature could favor dormancy breaking and lead to early and synchronized flowering in response to forcing conditions in C. japonica ‘Nuccio’s Pearl’. Plants with fully developed floral primordia were stored at dark, 7°C, and RH>90% for up to 8 weeks. To monitor endodormancy release during the storage, we evaluated the content of ABA in flower buds and the expression profiles of five putative genes related to dormancy and cold acclimation metabolism in leaves and flower buds. In addition, the expression of four anthocyanin biosynthesis pathway genes was profiled in flower buds to assess the effect of the treatment on flower pigment biosynthesis. At 0, 4, 6, and 8 weeks of cold treatment, 10 plants were transferred to the greenhouse and forced to flower. Forced plant flower qualities and growth were observed. The abscisic acid content and the expression profiles of two dormancy-related genes (CjARP and CjDEH) suggested that dormancy breaking occurred after 6-8 weeks of cold treatment. Overall, plants treated for 6-8 weeks showed earlier vegetative sprouting, enhanced and homogeneous flowering with reduced forcing time. Prolonged cold treatments also reduced flower size and longevity, anthocyanin content, and pigment biosynthesis-related gene transcripts. In conclusion, the cold treatment had a promotive effect on dormancy breaking but caused severe drawbacks on flower quality.